Shear Strengthening of Composite Steel-Concrete Girders with Web Openings Using CFRP Sheets - Shawky AbdulSahib, Wael; J. Hamood, Mohammed; Mohammed Majeed, Ahmed (International Journal of Engineering and Technology, 2018)
This study presents an experimental investigation of subjecting one-point load at mid-span of five composite steel-concrete girders that are loaded predominantly in shear. Three of girders are reference girders with no web openings, square web openings, and circular web openings, respectively. The both other girders are strengthened girders. The compressive strength of concrete, slab reinforcement and all dimensions of girders are kept. The CFRP laminates were adhesively attached to the webs of strengthened girders in various patterns and were done to estimate the effect of strengthening scheme by CFRP composite on increasing of the ultimate load capacity of the web openings girders. The research purposes to examine the behavior and effect of increasing in the ultimate shear capacity of strengthened girders that have constant dimensions and locations of web openings which is about 40 % of web depth. The results show the increase in ultimate load capacity of strengthened girders containing square and circular web openings with about 23.75% and 25.9%, respectively compared to that of reference girders. Furthermore, the ultimate shear strength was predicted by von Mises stresses were used for girders without and with square and circular web openings.Â Â